Prevalence of Von Willebrand Disease in Women of Reproductive Age With Heavy Menstrual Bleeding in Kashan, Iran, During 2019 - Tahereh Abdoli; Mansooreh Samimi; Fatemeh Atoof; Mohammad Shayestehpour; Majid Ehsani (Shahrekord University of Medical Sciences, 2020)
Background and aims: Von Willebrand disease (VWD) is an inherited disorder of blood clotting in humans. The prevalence of VWD is different among various populations. The prevalence of this disorder in women with menorrhagia is less reported in Asia and Iran. The present study aimed to determine the prevalence of VWD in women of reproductive age with heavy menstrual bleeding (HMB).   Materials and Methods: A total of 160 women in the reproductive age group (15-45 years) with HMB who referred to the hematology clinic of Kashan Shahid Beheshti hospital during 2019 participated in this cross-sectional study. Demographic characteristics, clinical testing, and physician-reported problems of each participate including age, menstrual cycle length, uterine myoma, and polyp were collected using a questionnaire, sonography, and physical examination of women by a physician. The laboratory tests included hemoglobin (Hb), ferritin, iron, and total iron-binding capacity (TIBC).   Results: Fifteen patients (9.3%) with severe menstrual bleeding had VWD with a mean age of 34.60±6.85 years. The frequency of the uterine fibroid (myoma) in women with VWD was significantly higher than that in patients without VWD (p =0.03). The mean ferritin level among 15 women with VWD and 145 women without VWD was 23±4.28 ug/dL and 30.68±4.46 ug/dL, respectively (p =0.001). The mean serum iron in total participants was 35.3±11.48 ug/dL and VWD patients had a lower iron level compared to those without VWD (p =0.001). There was not a significant difference in TIBC level between women with and without VWD (p =0.6).   Conclusion: Based on the results, 9.3% of women of reproductive age with HMB in Kashan, Iran, had VWD, which is lower compared to other regions of Asia.